Long-term results of hybrid aortic arch repair using landing zone 0: a single-centre study. (13th February 2021) - Kudo, Tomoaki; Kuratani, Toru; Shimamura, Kazuo; Sakaniwa, Ryoto; Sawa, Yoshiki
Abstract:  : OBJECTIVES: Thoracic endovascular aortic repair (TEVAR) has been gradually extended to the aortic arch region, with improved results. However, the rates of strokes and endoleaks in a hybrid TEVAR remain high. The goal of this study was to clarify the effectiveness of a hybrid TEVAR with a zone 0 landing using our treatment strategy. METHODS: From April 2008 to March 2020, a total of 102 patients were enrolled in this study, with a median follow-up period of 3.2 years. The procedures included total debranching TEVAR with graft replacement of the ascending aorta in 62 patients, total debranching TEVAR with ascending aorta banding in 19 patients and total debranching TEVAR without ascending aorta banding in 21 patients. RESULTS: Thirty-day mortality and hospital deaths were 1.0% ( n  = 1) and 3.9% ( n  = 4), respectively. The rates of aortic complications and endoleaks during the first 30 days postoperatively were 8.8% ( n  = 9) and 4.9% ( n  = 5), respectively. There was no type 1a endoleak, whereas retrograde type A dissection occurred in 2 (2.0%) patients. The rate of late aortic events was 3.9% ( n  = 4); there were no late endoleaks or aneurysm ruptures. The 10-year survival rate was 73.7% [95% confidence interval (CI) 60.3–83.8%]. The 10-year rates of aorta-related deaths and aortic events when performing a competitive-risk analysis were 29.4% (95% CI 16.3–42.5%) and 7.2 (95% CI 23.0–51.4%), respectively. CONCLUSIONS: Satisfactory early and long-term results of a hybrid TEVAR with a zone 0 landing were achieved using our treatment strategy. When performing hybrid TEVAR in zone 0, postoperative aortic events may be reduced by accurate preoperative assessment of the ascending aorta.